Pengaruh Penggunaan Sosial Media Instagram Dan Electronic Word Of Mouth Terhadap Minat Beli Produk Erigo Pada Mahasiswa Fakultas Hukum Universitas Sumatera Utara - Ester Sembiring; Adelina Lubis; Ihsan Effendi (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2023)
This study aims to determine "The Effect of Social Media Use Instagram and Electronic Word Of Mouth on Interest in Buying ERIGO Products at the Faculty of Law, University Sumatera Utara" using an associative research type with the population being students of the Faculty of Law, University Sumatera Utara totaling 85 respondents as samples. The research data in this study was obtained through the distribution of questionnaires with the help of Google Form.Based on the results of the t test, it was found that the negative value of the tcount was -0.265, so it was known that the tcount ttable and the p-value in the Sig column. namely 0.791 0.05 which means no effect, so it can be interpreted that Instagram Social Media has no effect on buying interest in ERIGO Products at the Faculty of Law, University of UtaraSumatera. In the X2 (Electronic Word Of Mouth) test, it was found that the tcount value was 7.242, so it was known that the tcount ttable and the p-value in the Sig column. ie 0.000 0.05, which means that it has a positive and significant effect, so that it can be interpreted that Electronic Word Of Mouth has a positive and significant effect on buying interest in ERIGO Products at the Faculty of Law, University of Sumatera Utara. Based on the test results, it was found that the value of Fcount (55.221) Ftable (2.72) with a value of Sig. 0.000 0.05, then according to the existing theory, it shows that Instagram Social Media and Electronic Word Of Mouth together (simultaneously) have a positive and significant effect on Buying Interest in ERIGO Products at the Faculty of Law, University of Sumatera Utara. And the calculation of the coefficient of determination test (R2) Adjusted R Square value was found to be 0.564 (56.4%). This figure shows that 56.4% Buying Interest (dependent variable) which can be explained by Instagram Social Media and Electronic Word Of Mouth variables (independent variable). And the remaining 43.6% is influenced by other factors that cannot be explained in this study.